Comparison of IV dexketoprofen trometamol, fentanyl, and paracetamol in the treatment of renal colic in the ED: A randomized controlled trial - Al, Behçet; Sunar, Mehmet Mustafa; Zengin, Suat; Sabak, Mustafa; Boğan, Mustafa; Can, Basri; Kul, Seval; Oktay, Mehmet Murat; Eren, Şevki Hakan (W.B. Saunders, 2018)
Objective: In this study, we aimed to compare the analgesic efficacy of intravenous dexketoprofen trometamol, fentanyl, and paracetamol in patients presenting to the emergency department with renal colic. Materials and method: Data obtained from the emergency departments of Gaziantep University's Hospital for Research and Practice along with two other state hospitals in Gaziantep, Turkey between January 2016 and January 2017 was used for this study. A total of three hundred patients (n = 300), who presented to the ER with complaints most common to renal colic whose diagnoses were subsequently confirmed with Computerized Tomography were included in the study. Patients’ pain scores were recorded using the Visual Analogue Scale, at admission (immediately before drug administration), then at the 15th, and 30th minutes. SPSS 22.0 software package was used for analysis. p < 0.05 was considered significant. Results: At the 15th minute comparison, the efficacies of the three groups of drugs were not superior to one other, but at the 30th minute, dexketoprofen trometamol was statistically more effective than paracetamol and fentanyl. There was no statistically significant difference between fentanyl and paracetamol. The need for additional analgesia in the group receiving dexketoprofen trometamol was found to be lower. Dexketoprofen trometamol was statistically superior to the other two agents in achieving full analgesia at the end of the thirty-minute period. Fentanyl was found to be statistically significant in achieving moderate analgesia. Conclusion: As a Non-steroidal antiinflammatory drug dexketoprofen trometamol is superior to paracetamol and fentanyl in achieving analgesia and reducing the need for additional drugs for the treatment of renal colic.
Keywords: Analgesic; Dexketoprofen trometamol; Efficacy; Emergency department; Fentanyl; Paracetamol; Renal colic; Visual analogue scale